Why everything is hackable. (Economist, 2017)
The article discusses the cyber crimes and computer hackings that has taken place in central bank of Bangladesh, U.S. National Security Agency (NSA) and U.S. Democratic National Committee. The vulnerabilities of internet securities that stems from the basics of information technology, the culture of software development and growth of online business is discussed.